Engineering properties of different fiber-reinforced metakaolin-red mud based geopolymer mortars - Nazir, Khizar; Canpolat, Orhan; Uysal, Mucteba; Nis, Anil; Kuranli, Omer Faruk (ELSEVIER SCI LTD, 2023)
In this research, fiber reinforced metakaolin-red mud based geopolymer mortar was produced by using recycled concrete aggregate and industrial waste glass powder as filler materials. Three different types of fibers were used to reinforce the geopolymer mortar, namely brass-coated steel fibers, polyamide fibers, and polyethylene fibers, with four different proportions by volume (0.25%, 0.5%, 0.75%, and 1.00%). Experiments for compressive strength, flexural strength, splitting tensile strength, flexural toughness factor, ultrasonic pulse velocity, and abrasion resistance were conducted to investigate the influence of fibers on mechanical properties. Specific gravity, porosity, and water absorption tests were conducted to examine the physical properties. Additionally, Scanning Electron Microscopy (SEM) and X-Ray Diffraction (XRD) analyses were performed. The results indicate that 50% replacement of recycled concrete aggregate and glass powder as filler material yielded the optimum strength properties. Moreover, addition of fibers enhanced the strength properties of the geopolymer mortar, for instance, the mixture having polyethylene fibers with a fiber volume of 0.75% improved the flexural strength up to 48.72%, and the mixture containing steel fibers with a fiber fraction of 0.25% showed the highest value of splitting tensile strength and improved up to 40% when compared to non-fibrous control mixture. Polyethylene fiber-reinforced mixture showed a notable toughening impact and showed a flexural toughness factor up to 66.29% more than the control sample. The reason of this improvement is because of the bridging effect of fibers. According to the findings, the 0.25% steel fibrous samples showed the best result in terms of minimum weight loss due to abrasion and showed 36.08% more abrasion resistance compared to non-fibrous control mixture. Moreover, increase in porosity was observed in fiber-reinforced mixtures. The lack of CaO content is found responsible for poor mechanical strength and bending performance of fibrous metakaolin-red mud based geo-polymer mortars specimens.
Keywords: Geopolymer; Red mud; Recycled aggregate; Glass powder; Fly ash; Fibers; RECYCLED AGGREGATE CONCRETE; FLY-ASH; MECHANICAL-PROPERTIES; COMPRESSIVE STRENGTH; PORTLAND-CEMENT; CALCIUM FLY; WASTE GLASS; TEMPERATURE; BEHAVIOR; WORKABILITY; Construction & Building Technology; Engineering; Materials Science